Dendritic cells and the eye: their role in the ocular immune response - Forrester, John V. (Henry Stewart Talks, 2014)
Ocular inflammation (uveitis, corneal disease), Infectious and non-infectious, Role of antigen presenting cells (dendritic cells), Organ specific autoimmunity (retinal damage), Corneal graft rejection, Influence of immune privilege on ocular inflammation